METHODS FOR ANTIMICROBIAL SURFACE MODIFICATION OF MEDICAL GRADE POLYDIMETHYLSILOXANE - Yakushev, R.M.; Karpunina, T.I.; Yakusheva, D.E.; Kiselkov, D.M.; Borisova, I.A.; Kasatkin, I.A. (Perm Federal Research Centre Journal, 2017)
The methods and approaches to antibacterial treatment of polydimethylsiloxane (PDMS) with a view to use in medical devices, such as urinary catheters, and testing in the hospitals of Perm Krai have been developed. The antibacterial effect has been observed as a result of the transformation of the silicone rubber surface activated by ion-beam treatment and chemical etching. The surface of the silicone rubber devices and synthesized samples has been modified by grafting of acrylic acid, application of chemisorption of zinc oxide nanoparticles, chelation of zinc compounds grafted with amino functional groups, grafting of perfluorinated groups, chemical vapor deposition of submicron zinc oxide particles. The biofilms of S. aureus, S. epidermidis, P. aeruginisa, K. pneumoniae have been analyzed by photometric methods, FTIR spectroscopy, and optical and scanning electron microscopy. It has been shown that all the samples tested have antibacterial activity, however, the most pronounced effect has been observed in the case of the surface layers with introduced zinc and fluorine compounds.